Teaching Visual Arts: from the Innocent Eye to Immersiveness and Vice Versa - Richter, Marijan (Revija za elementarno izobraževanje, 2017)
In the mid-19th century, John Ruskin, apologist for the poetics of the innocent eye, advocated a break with academic Realism. A century later, Gombrich and Goodman criticized Ruskin's Romantic subjectivism from the position of High Modernism. Consequently, the "Enlightenment" approach in teaching visual arts became stronger. Recently, some teaching specialists have been trying to inaugurate the term, immersiveness, in place of visual arts language for the purpose of introducing contemporary art into the syllabus.This paper examines the relation between "the innocent eye myth" and topical approach of "immersiveness" within the framework of educational objectives and methods in contemporary teaching.
Keywords: innocent eye; immersiveness; visuality; child's artistic expression; motivation for creating artwork